Design, implementation, and evaluation of dialogic classroom talk in early childhood education. (June 2021) - van der Veen, Chiel; Michaels, Sarah; Dobber, Marjolein; van Kruistum, Claudia; van Oers, Bert
Abstract: The aims of the present study were to design and implement an intervention focused on dialogic classroom talk in early childhood education and to evaluate what it may contribute to children's oral communicative competence. Together with four teachers we developed and implemented an ecologically valid intervention that supports teachers to use several dialogic talk moves. We evaluated our intervention using a one-group pretest-posttest design. Discourse analysis of pre- and post-observations of classroom talk revealed that teachers used more dialogic talk moves over the course of our intervention. Pre- and post-tests of children's ( N  = 92) oral communicative competence indicated that our intervention significantly relates to an increase of children's communicative competence. Furthermore, analysis of pre- and post-observations of classroom talk showed an increase in the use of key linguistic features of oral communicative competence in the participating children. Although the set-up of the studies does not permit propositions about causal relationships, the results of this study show that dialogic classroom talk can be promoted even in early childhood education, and give reasons to suppose that further studies may show that this might be beneficial for children's oral communicative competence.